Flexible work arrangements in open workspaces and relations to occupational stress, need for recovery and psychological detachment from work - Mache, Stefanie; Servaty, Ricarda; Harth, Volker (Journal of occupational medicine and toxicology (London, England), 2020)
Background The trend is going into the direction of flexible work arrangements in open workspaces in which employees can decide where and when to work. The aim of this study was to analyze effects of a transition to open workspaces including Activity Based Working (ABW) on employees’ working conditions and their levels of occupational stress, need for recovery and psychological detachment from work. Methods Employees of a large technology company responded to a baseline and two follow-up measurements over one year. Data were collected via online survey assessing the employees’ mental demands, workload, job autonomy, support from supervisor, team collaboration, satisfaction with communication climate and three well-being outcomes (occupational stress, need for recovery and psychological detachment from work). Descriptive statistical analyses, analyses of variance and regression analyses were applied to test the hypotheses. Results Significant differences in working conditions were found after the transition, e.g. reduced mental demands, but an increased workload. Job autonomy, team collaboration and satisfaction with communication climate increased. Levels of occupational stress decreased significantly over time. Regression analyses revealed substantial associations between flexible work arrangements, job resources and occupational stress. Conclusion The results contribute to the current knowledge on flexible work arrangements in open work spaces. They can be used to design future work settings aimed at increasing employees’ well-being and job performance. Further practical implications and recommendations for future research are discussed.